Motives for sharing illness experiences on Twitter: conversations of parents with children diagnosed with cancer. Issue 4 (3rd April 2018) - Rehman, Sameen; Lyons, Kelly; McEwen, Rhonda; Sellen, Kate
ABSTRACT: A patient- and family-centred approach in paediatric health care is important because parents are involved in making key decisions about their child's health care and advocating for the best interest of the child. Parents and family members are increasingly turning to the internet to find and actively share information about their child's health care. Twitter is one of many online platforms used by parents of children diagnosed with cancer to share information related to their child's cancer experience. Existing research suggests that there is a need to better understand the motives for using Twitter for sharing content about a child's cancer experience. Furthermore, there is a lack of theoretical frameworks for characterizing those motives. In this paper, we identify key themes of tweets posted by parents of children diagnosed with cancer and align those themes with motives inspired by the well-studied Everyday Life Information Seeking framework. We propose a new motive in addition to those associated with the framework and suggest that information can be shared for endogenous reasons as well as to meet the needs of others. This paper contributes an increased understanding of motives for sharing information about a child's cancer journey and extends a theoretical framework for building further knowledge in this area.